"I am here for a reason": minority teachers bridging many divides in urban education. Issue 3 (4th May 2018) - Magaldi, Danielle; Conway, Timothy; Trub, Leora
Abstract: Minority teachers are overwhelmingly employed in urban schools in underserved, low-income communities with large minority student populations. They receive little in the way of multicultural preparation, mentorship, and professional induction to meet the demands of teaching diverse student populations. This grounded theory study explores the experiences of novice teachers from various minority backgrounds working in urban classrooms. A tentative grounded theory, 'I am here for a reason' emerged, suggesting that minority teachers rely on their personal backgrounds and experiences to help them take an insider's perspective with minority students in light of poor multicultural preparation and limited support in schools. The shared cultural perspective with students enables teachers to connect with and advocate for students, which represents both a strength and challenge for minority teachers. Finally, minority teachers are motivated by a strong desire for social justice as they work to bridge many divides, and are intentional in their work despite facing significant obstacles in training and teaching.